Efektivitas Metode Quantum Writing Terhadap Keterampilan Menulis Cerpen - Afra Madina Sari; Elvrin Septyanti; Oki Rasdana (Jurnal Muara Pendidikan, 2026)
This study aims to determine the effect of the Quantum Writing learning method on the short story writing skills of tenth-grade students at SMK KANSAI Pekanbaru. The study used a quantitative approach with a quasi-experimental method. The study sample consisted of 51 students, consisting of class X TKR as the experimental class and class X TKJ/TITL as the control class, selected using a purposive sampling technique. Data collection was conducted through short story writing tests in the form of pretests and posttests. Data were analyzed using descriptive and inferential statistics with the help of SPSS version 31, including normality tests, homogeneity tests, and Independent Samples t-tests. The results showed that the average score of students' short story writing skills in the experimental class increased significantly from 63 to 83, while in the control class it increased from 61 to 69. The results of the Independent Samples t-test showed a Sig. (2-tailed) value <0.05, indicating a significant difference between the two classes. Thus, it can be concluded that the Quantum Writing learning method has a significant and effective influence in improving the short story writing skills of 10th-grade students at SMK KANSAI Pekanbaru.